Human Resources Management System in Digital Economy (Empirical Study on Elcom+) - Hartomy Akbar Basory; Muhamad Danny Pratama*; Sherla Margaretha (Universitas Syiah Kuala, 2024)
This research uses qualitative analysis method techniques and data collection using observation, depth interviews, questionnaires, and comparative analysis techniques. This research analyzes the trends in human resources management systems, and HRMS in the digital economy implemented by the Russian company, Elcom+ LLC. The problem and subject matter of this research are how to study the trends of HRMS in the digital economy in improving company performance, and whether the analysis of suitable international experience and Russian HRM practices has an impact on improving company performance. The result is an effective modern HRM supported by the disciplines of digital management, site development technology, HRM knowledge, and innovation management and offers a favorable system for the application of new methods of recruiting and selecting employees, to attract talent, motivate, stimulate employees, and also timeliness is a virtue. Therefore, the purpose of this research is to study the trends of HRMS in the digital economy through the analysis of international experience and find the analysis of international experience and HRM practices of enterprises in Russia. The results of this study have an impact on HRM and corporate financial management. Furthermore, the conclusion of this research is the potential role of HR designed to meet the challenges of automation and digital transformation in organizations and agile work culture. Moreover, the results outline that HRM systems can be compared, developed, and additionally applied to the digital economy system with the support of site development technology and cloud systems.